Language Acquisition, as a Predictor of School Learning and Inclusion Variable (London Journal of Research In Humanities and Social Sciences, 2025)
This article intends to share the concern about the school integration ofchildren born with biological disadvantages due to their prematurity. These children born prematurely, as a result of their immaturity, suffer from a number of pathologies that require special care in neonatology units and a subsequent follow-up by an interdisciplinary team of professionals to minimize their sequelae and to fully develop their capabilities.Compared to full-term infants, premature and low-weight babies have a number of characteristics that place them at high risk. In addition, the aim herein is to find out if they required support, if they received therapeutic assistance, if the family accompanied them throughout this process and upon reaching school age, in order to show whether they experienced difficulties in their school integration (such as difficulties in learning to read and write, for instance).
Keywords: educational inclusion; premature baby; child development; learning difficulty